2001
DOI: 10.3354/ame024083
|View full text |Cite
|
Sign up to set email alerts
|

Trophic interactions between zooplankton and the microbial community in contrasting food webs: the epilimnion and deep chlorophyll maximum of a mesotrophic lake

Abstract: Trophic interactions between the mesozooplankton and the microbial web (bacteria, protozoa) were studied in 2 in situ grazing experiments in the epilimnion and the deep chlorophyll maximum (DCM) of a mesotrophic lake. We combined the Landry-Hassett dilution technique, whereby growth and grazing rates can be determined simultaneously, with the presence or absence of mesozooplankton and additional nutrients. The epilimnion was cladoceran-dominated, and had relatively high ciliate, and low heterotrophic nanoflage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…can also consume other HF . Among metazoa, several studies have provided evidence that cladocerans are the main grazers of HF (Köthe & Benndorf, 1994;Jürgens & Stolpe, 1995;Jürgens & Jeppesen, 2000;Adrian et al, 2001;Auer and Arndt, 2001), as well as of small ciliates and bacteria (Hartmann et al, 1993;Jürgens & Jeppesen, 2000). Several studies have highlighted that rotifers and copepods are also able to consume small ciliates and HF in the size range of 20-50 lm (Dolan & Gallegos, 1991;Arndt, 1993;Sanders et al, 1994;Adrian & Schneider-Olt, 1999;Jürgens & Jeppesen, 2000;Zöllner et al, 2003;Bundy et al, 2005).…”
Section: Hf Are Key Intermediates In the Food Chainmentioning
confidence: 95%
“…can also consume other HF . Among metazoa, several studies have provided evidence that cladocerans are the main grazers of HF (Köthe & Benndorf, 1994;Jürgens & Stolpe, 1995;Jürgens & Jeppesen, 2000;Adrian et al, 2001;Auer and Arndt, 2001), as well as of small ciliates and bacteria (Hartmann et al, 1993;Jürgens & Jeppesen, 2000). Several studies have highlighted that rotifers and copepods are also able to consume small ciliates and HF in the size range of 20-50 lm (Dolan & Gallegos, 1991;Arndt, 1993;Sanders et al, 1994;Adrian & Schneider-Olt, 1999;Jürgens & Jeppesen, 2000;Zöllner et al, 2003;Bundy et al, 2005).…”
Section: Hf Are Key Intermediates In the Food Chainmentioning
confidence: 95%
“…Others have found that phytoplankton migrate between strata (Tilzer 1973;Gasol et al 1992), and our limnocorrals contained many flagellated species capable of movement (chrysophytes, cryptophytes, and dinophytes). Removal of macrozooplankton from the limnocorrals may also have allowed microzooplankton to proliferate and graze heavily on the picoplankton that were most abundant in the DCL (Adrian et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Copepod grazing may indirectly have a negative effect on the total grazing pressure on zoospores because copepods have higher clearance rates for ciliates than they do for small flagellates such as P. piscicida zoospores (Stoecker & Sanders 1985, Gifford & Dagg 1988, Hansen et al 1994. Microzooplankton populations, particularly planktonic ciliates, respond quickly to changes in mesozooplankton abundance, and, in turn, microzooplankton strongly control <15 µm flagellates (Miller et al 1995, Adrian et al 2001.…”
Section: Discussionmentioning
confidence: 99%